Genetic diversity analysis in tomato (Solanum lycopersicum) using microsatellite markers - KUMAR, MANISH; YADAV, R K; BEHERA, T K; TALUKDAR, AKSHAY; ARORA, AJAY (The Indian Journal of Agricultural Sciences, 2018)
Present study was conducted to determine the genetic diversity at molecular level among 21 thermo-tolerant tomato accessions. All the accessions were screened by using 18 simple sequence repeats (SSR) primers to estimate genetic diversity and genetic relationships among these accessions. Among the 18 SSRs, only 5 primers (SSR47, TES628, TGS149, TGS230 and TGS330) were polymorphic which were used for accessing the genetic distance to find out the phylogenetic relationship among the different tomato accessions. Polymorphism information content (PIC) ranged from 0.17 (TGS230) to 0.36 (TGS149) with average PIC as 0.30. Unweighted pair group method with arithmetic mean (UPGMA) clustering grouped the accessions into two main clusters. The information related to genetic diversity presented in this study might be useful to breeders for planning crosses among these accessions for future tomato breeding programmes.